Developmental and physical-fitness associations with gross motor coordination problems in Peruvian children. (June 2016) - de Chaves, Raquel Nichele; Bustamante Valdívia, Alcibíades; Nevill, Alan; Freitas, Duarte; Tani, Go; Katzmarzyk, Peter T.; Maia, José António Ribeiro
Highlights: Girls are more likely to suffer from gross motor coordination (GMC) problems than boys. More mature children and who live at the jungle area are less likely to have GMC problems. Children with greater BMI are more likely to have GMC difficulties. Children with GMC problems are also those with lower physical fitness levels. Abstract: The aims of this cross-sectional study were to examine the developmental characteristics (biological maturation and body size) associated with gross motor coordination problems in 5193 Peruvian children (2787 girls) aged 6–14 years from different geographical locations, and to investigate how the probability that children suffer with gross motor coordination problems varies with physical fitness. Children with gross motor coordination problems were more likely to have lower flexibility and explosive strength levels, having adjusted for age, sex, maturation and study site. Older children were more likely to suffer from gross motor coordination problems, as were those with greater body mass index. However, more mature children were less likely to have gross motor coordination problems, although children who live at sea level or at high altitude were more likely to suffer from gross motor coordination problems than children living in the jungle. Our results provide evidence that children and adolescents with lower physical fitness are more likely to have gross motor coordination difficulties. The identification of youths with gross motor coordination problems and providing them with effective intervention programs is an important priority in order to overcome such developmental problems, and help to improve their general health status.